Formulasi dan uji sifat fisik granul effervescent ekstrak kunyit asam (Curcuma longa-Tamarindus indica). - Kautsari, Farah Widya; Emha, Maulida Rahmawati (Fakultas Farmasi Universitas Tjut Nyak Dhien, 2025)
Empirically, turmeric tamarind is used to relieve pain and inflammation and ease menstrual cramps. However, conventional herbal preparations are currently less popular, especially among teenagers. Effervescent turmeric tamarind formulations are an innovative, practical pharmaceutical preparation with the advantage of a pleasant taste, which helps disguise the bitter flavor of turmeric. This product also provides a refreshing effect due to the acid-base reaction that produces carbon dioxide (CO2). This study aims to evaluate the physical test of effervescent turmeric tamarind granules. This experimental study formulates three turmeric-tamarind effervescent granule formulas by varying the turmeric extract dosage (Curcuma longa) to 250 mg, 500 mg, and 750 mg. The evaluations performed include organoleptic tests, water content, flow properties and angle of repose, dissolving time, and pH testing. The results showed that turmeric extract (Curcuma longa) and tamarind (Tamarindus indica) can be formulated into effervescent granules—the three formulas with different variations of turmeric extract produced good physical quality test results. Variations in the concentration of turmeric extract did not affect the physical quality of the granules.